The Progress in Exploratory Studies of Peripheral Blood Single Nucleated Cells as Seed Cells in Peripheral Nerve Repair - Yi Chen; Yubin Wen; Mingyue Zhang; Jing Nie; Guangfeng Sun (Neural Plasticity)
Peripheral nerve injury (PNI) represents a prevalent clinical condition, often resulting from mechanical trauma or tumor resection, which frequently induces persistent sensory deficits, motor impairment, neuropathic pain, or paralysis. Consequently, substantial socioeconomic burdens are imposed on affected individuals. Autologous nerve transplantation is often considered the preferred approach for reconstructing peripheral nerve defects; however, this technique is associated with limitations including donor-site sensory loss, restricted graft length, and nerve mismatches. Recently, peripheral blood mononuclear cells (PBMCs) have emerged as a focal point in nerve regeneration research due to their accessibility, immunomodulatory properties, and neuro-reparative potential. Nevertheless, the precise mechanisms underlying PBMC-mediated nerve repair remain incompletely characterized, and their molecular pathways require further elucidation. This study explores the potential role of PBMCs in promoting peripheral nerve regeneration, with a particular focus on their regulation of retrograde brain-derived neurotrophic factor (BDNF) transport through modulation of Hook1 expression and associated molecular pathways. This research seeks to provide novel insights for PBMC-based therapeutic strategies and establish a theoretical foundation for clinical translation. Implementation challenges and translational prospects for PBMCs in nerve regeneration are also critically evaluated.